2019
DOI: 10.1039/c8ew00899j
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for rotating belt filters in novel wastewater treatment plant configurations

Abstract: The combination of rotating belt filters and chemically enhanced settling allowed the production of suitable effluents for further stages and to generate enough methane to reach energy autarky.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 50 publications
4
9
0
Order By: Relevance
“…RBF‐S with the highest TS content contained 1.55 ± 0.058 g COD/TS and 0.28 ± 0.08 g CBOD 5 /TS, corresponding to an average COD biodegradability (f COD_CBOD5 ) of 5.7 g COD/g BOD (Table 6). Observed high COD concentration and low contents of TKN (20 to 23 mg N/g TS) and TP (5.6 to 6.5 mg P/g TS) of RBF‐S were consistent with previously reported results for retained solids by the pilot‐scale and full‐scale 350‐μm RBF (Da Ros et al, 2020; Ghasimi et al, 2015; Taboada‐Santos et al, 2019).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…RBF‐S with the highest TS content contained 1.55 ± 0.058 g COD/TS and 0.28 ± 0.08 g CBOD 5 /TS, corresponding to an average COD biodegradability (f COD_CBOD5 ) of 5.7 g COD/g BOD (Table 6). Observed high COD concentration and low contents of TKN (20 to 23 mg N/g TS) and TP (5.6 to 6.5 mg P/g TS) of RBF‐S were consistent with previously reported results for retained solids by the pilot‐scale and full‐scale 350‐μm RBF (Da Ros et al, 2020; Ghasimi et al, 2015; Taboada‐Santos et al, 2019).…”
Section: Resultssupporting
confidence: 91%
“…Observed high COD concentration and low contents of TKN (20 to 23 mg N/g TS) and TP (5.6 to 6.5 mg P/g TS) of RBF-S were consistent with previously reported results for retained solids by the pilot-scale and full-scale 350-μm RBF (Da Ros et al, 2020;Ghasimi et al, 2015;Taboada-Santos et al, 2019). The characteristics of the retained solids by the DF and PC treatments versus those by the RBF, in both the PAR and SER configurations, showed a lower COD to TS ratio (0.97 to 1.18 vs. 1.52 to 1.55 g COD/g TS; Table 5) and a higher biodegradability (4.1 to 5.1 vs. 5.7 to 5.9 g COD/g CBOD 5 ; Table 6) despite a much lower TS content (0.6% to 1.4% vs. 4.37%; Table 2).…”
Section: Chemical and Biological Characteristics Of Solids Fractionssupporting
confidence: 92%
See 1 more Smart Citation
“…The main difference between PFs and RBFs is the medium pore size, which will influence the treatment performance and overall operational costs. While PFs achieves 75%–85% TSS and 45%–60% COD reduction (Caliskaner et al., 2015; Caliskaner, Tchobanoglous, Young, & Laybourne, 2014) by using a relatively smaller pore size (i.e., 5–10 μm), the RBF reaches lower treatment removal of 20%–40% TSS and 30%–40% COD (Ho et al., 2017; Taboada‐Santos, Lema, & Carballa, 2019) due to the much larger size of the mesh pores (i.e., 100–500 µm). However, in both cases, the TSS removal efficiency can be significantly higher than the TSS removal (50%–60%) from conventional primary clarifiers operated at typical design conditions (Metcalf & Eddy, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A great effort has been made over the last two decades to determine the occurrence of OMPs in wastewater and their fate in the different units of conventional WWTPs, such as primary clarifiers (Behera et al, 2011;Carballa et al, 2004), activated sludge reactors (Alvarino et al, 2014;Radjenović et al, 2009;Santos et al, 2009;Suarez et al, 2010) or anaerobic digesters (Gonzalez-Gil et al, 2016;Narumiya et al, 2013;. However, these novel technologies are yet at their early stages of industrial implementation, although preliminary works studying the fate of OMPs in RBF systems (Taboada-Santos et al, 2019b), HRAS reactors and CEPT (Taboada- , PN-AMX reactors (Alvarino et al, 2015;Kassotaki et al, 2018;Laureni et al, 2016) or sludge TH (Reyes-Contreras et al, 2018;Taboada-Santos et al, 2019a;Zhang and Li, 2018) can already be found in the literature. However, these units are commonly studied individually, so it is essential to integrate multiple units to holistically assess the fate of OMPs in novel WWTPs.…”
Section: Introductionmentioning
confidence: 99%